Peranan Google Earth Sebagai Media Pembelajaran Untuk Meningkatkan Hasil Belajar Sejarah Pada Kelas X TAV SMK N 2 Pematangsiantar T.A 2023/2024 - Mesra Elisabet Situmorang; Asnewastri; Jalatua H. Hasugian; Satria Chandra (Prodi Pendidikan Sejarah FKIP USI, 2024)
Google Earth is an interactive mapping application released by Google which displays a 3D map of the world, topographic conditions, satellite photos of terrain which can be overlaid with roads, buildings, locations or other geographic information.The purpose of this research is to find out: (1) how much improvement in student learning outcomes after learning by using Google Earth. This research is a quasi-experimental research with a nonequivalent control group design. The independent variable of this research is learning using Google Earth media, and the dependent variable is learning outcomes. The population of this study was all students in class X of SMK N 2 Pematangsiantar. The samples in this research were X TAV 2 as the experimental class and X TAV 1 as the control class. Data collection is carried out by observation, learning results tests and documentation. The data analysis technique used is quantitative data analysis using descriptive statistics. Hypothesis testing uses t-test. The results of the research show that students' understanding of learning before learning between the experimental and control classes from the hypothesis test of the average pretest score showed that there was no influence/difference in the results before treatment. However, after the experimental class learning treatment that used internet-based media, the results were much higher than the control class that did not use the internet, which can be shown by the value of tcount > ttable, namely 3,578 > 2.004, so the results of the hypothesis test showed that there was an influence of internet use on students' learning understanding. Meanwhile, in the experimental class, from hypothesis testing, the average pretest and posttest scores can be shown by the pretest average score < posttest average score 41,4 < 82.5, so there is a significant increase in learning understanding between before and after treatment. Based on the results of this research, it can be concluded that the use of the internet has an influence on students' learning understanding. class X SMK N2 Pematangsiantar